The genome of infectious bursal disease virus consists of two segments of double-stranded RNA. - Müller, H (1979)
The RNA of infectious bursal disease virus was reexamined in a detailed analysis. It could be established that its genome consists of two segments of double-stranded RNA. The RNA is RNase resistant and has a sedimentation coefficient of 14S and a buoyant density of 1.62 g/ml. The purine/pyrimidine ratio is nearly 1; the guanine plus cytosine content is 55.3%; the Tm is 95.5 degrees C. The molecular weights of the two double-stranded segments were determined to be 2.2 x 10(6) and 2.5 x 10(6).